Low Complexity PMI Selection for BICM-MIMO Rate Maximization in 5G New Radio Systems - Maleki, Marjan; Jin, Juening; Haardt, Martin (2023 31st European Signal Processing Conference (EUSIPCO), 2023)
This paper presents novel methods for selecting the best precoding matrix index (PMI) from the Type- I codebook adopted in 5G New Radio (5G NR (\text{gNB}) , in terms of the achievable rate for MIMO-BICM systems. To overcome the complexity of dealing with a multi-variable problem with discrete domains, we introduce heuristic algorithms that exploit the Kronecker and DFT structure of the codebook. Our proposed methods utilize a combination of direct estimation and a low-dimensional search to derive the optimal PMI indices, and the singular value (SV) pre-coder serves as an optimal reference. The approach significantly reduces the number of codebook precoder candidates, resulting in a much lower complexity compared to the exhaustive search methods. Simulation results demonstrate the effectiveness of our proposed algorithms in achieving a performance comparable to the performance obtained by an exhaustive search.